Acoustic Ray-Trace Correction for UUVs Cooperative Localization in Deep Ocean Applications. Issue 6 (2nd November 2022) - Du, Zhenqiang; Chai, Hongzhou; Li, Zeyu; Xiang, MinZhi; Zhang, Fan; Hui, Jun
Abstract: Precise position of Unmanned Underwater Vehicles (UUVs) plays a decisive role in optimal formation control, reasonable path planning, and efficient cooperative operation. However, the traditional method has the deficiency of low ranging accuracy and contains systematic deviation in the deep ocean applications, which seriously affects the accuracy of UUVs position and makes the goal of UUVs optimal configuration no longer applicable. A novel acoustic ray-trace correction method is proposed for UUVs cooperative localization in deep ocean applications. Considering the bending of underwater sound ray and the variation of sound velocity, the model of UUVs cooperative localization based on ray-trace correction is established. Two master UUVs in shallow ocean and one slave UUV in deep ocean under five configurations are simulated. The experimental results show that the average position bias of UUVs cooperative localization under the five configurations are reduced by 57.97%, 62.29%, 68.51%, 74.93% and 82.54%, respectively, which can expand the application scenarios of UUV. Furthermore, the proposed method can overcome the drawback of systematic deviation in the traditional method, so as to be consistent with the goal of UUVs optimal configuration.